Determining Key Performance Indicators With Balanced Scorecard Approach For Construction Project Warehouse Efficiency - Durio Etgar; Dermawan Wibisono (Journal of Economics and Business UBS, 2023)
Recent Covid-19 pandemic had negative impacts on various formal industries in Indonesia. Many companies needed to stop operating because of disrupted supply chain, others had to lay off their employees. This adverse condition also affected PT Waskita Karya (Persero) Tbk, reflected from the slump in company’s business revenue. Waskita was forced to readjust their strategies to coupe with the situation by introducing “Sustainable Growth” grand strategy namely Maximize cash inflow from project payment and land acquisition credit, Tollroad divestation, credit relaxation proposal, and OPEX efficiencies. OPEX efficiencies is the one that possibly managed by project for now. Moreover, efficiencies are the most relevant, potentially permanent, and long-term strategy to reach “Sustainable Growth” vision and can be applied throughout the company. Efficiency in construction project warehouse is currently unmanageable because there is no proper Performance Management System for measuring the achievement. It is quite contradictive with the fact that warehousing process contains moreless 30% of project financing. Developing and tracking Key Performance Indicators (KPI) with Balanced Scorecard (BSC) approach had been seen as the solution as it is covering four important perspectives of performance namely financial, customer, internal process, and learning and growth. BSC is considered holistic and comprehensive enough to bolster the warehouse efficiency. The development of BSC for construction project warehouse was involving the vision derivating process, which is efficiency. That vision has been derived into 16 strategic objectives by analyzing the internal and external factor of Waskita’s construction project warehouse using SWOT and TWOS Matrix analysis. Those objectives will later be translated into 28 Key Performance Indicators to measure the objective achievement with the proportion of 7 financial indicators, 6 customer indicators, 9 internal process indicators, and 6 learning and growth indicators. The process of gaining consensus and set the priorities towards the proposed BSC framework was involving 10 experts from Waskita with certain criteria that represent the demographic of stakeholders. The qualitative result will be analyzed and quantified using Fuzzy Delphi Method (FDM). FDM is a multi criteria decision making tool which is a modified version of the Delphi Method that incorporates elements of fuzzy logic to allow for uncertainty and subjectivity in the decision-making process. It converts linguistic variables into fuzzy numbers, which represent a range of values rather than a specific value. The analysis had been conducted with the results of all Balanced Scorecard perspectives (Financial, Customer, Internal Process, and Learning and Growth) are deemed applicable for Waskita’s construction warehouse based on the result of expert consensus with the financial perspective became the top priority. Furthermore, 21 out of 28 Key Performance Indicators had been agreed as the performance measurement for Waskita’s construction warehouse, with the proportion of 5 financial indicators, 4 customer indicators, 6 internal process indicators, and 6 learning and growth indicators. Those indicators had been translated from strategic objectives that could lead to efficiency. Order fulfillment rate became the most important indicator to track. Performance scoring system has been determined to categorize the performance indicators’ achievement of Waskita’s construction warehouse by the range of high, medium, and low with specific targets for each indicator. Waskita’s Project Manager has given the validation and willingness to implement the BSC. However, the development phase of determining indicator weight and initiatives should be continued to complement the existing research.